Trichobezoar in Two Children - E. M. Halimun; E. Kandouw; A. Arianto; S. Safiun (Indonesian Pediatric Society, 1992)
Two cases of trichobezoar in females of 11 and 12 years respectively have been presented. Trichophagia as a common habit or it could be a sign of emotional tension. Etiological clues should be sought and the underlying stress be removed and ameliorated.